Intrepretative Phenomenological Analysis: Perception of Health Risk of Smoking and Smoking Cessation Among Pharmacy Students - Amelia Lorensia; Anggara Martha Pratama; Ananta Yudiarso (ANIMA Indonesian Psychological Journal, 2016)
Smokers can experience addiction that impedes their efforts to quit smoking. Smokers’ perception and view of quitting smoking are worthy input for health practitioners to promote smoking cessation programs. The purpose of this study was to explore the perception of health risks of smoking and smoking cessation. The method was based on the phenomenological perspective using interpretative phenomenological analysis involving pharmacy students. The study was conducted over two years using snowball-purposive sampling. Participants were smokers who started smoking when they were 18 years old and had previously tried to quit smoking. Results showed that participants started smoking because of curiosity and influences from environments. All participants understood the risks of smoking, and had tried to quit smoking because smoking affected their health and economical status. Therefore, health programs need to focus on smokers’ behavior and barriers to quitting smoking since those who have good knowledge on the risks of smoking can experience difficulty in quitting smoking.